Gastrointestinal stromal tumours: a clinico-pathological study - Satwik, Nuvvula; Francis, Joseph; Mathias, Natasha (International Surgery Journal, 2021)
Background: The aim was to evaluate the clinical presentation, histopathological findings and immunohistochemistry in gastrointestinal stromal tumour (GIST) to better understand the disease. Methods: Patients admitted and suspected to have GISTs in the Departments of General Surgery and Oncology, Yenepoya Medical College from the period of October 2016 to October 2018 were included in the study. Results: From October 2016 to October 2018, 10 patients had been diagnosed with gastro-intestinal stromal tumour in Yenepoya Medical College. Out of the 10 patients 7 were males and 3 females. The age distribution showed that more than 70% of the cases were above the age of 55 years. Stomach was the most common site of GIST. The most common histopathological type was spindle cell type of GIST, and 70% of the GISTs came positive for CD117. Conclusions: To conclude, Gastro intestinal stromal tumours are a rare entity. In this study conducted in a tertiary centre only ten cases were reported in a span of two years of the study period. Further analysis of age and gender distribution, histopathological and immunohistochemistry of these tumours suggested that in majority, age group was found to be above 55 years, with male preponderance. Commonest site was stomach (40%) followed by jejunum. Common histopathological finding was found to be spindle cell variant. 70% cases were CD117 positive with more than 5 mitotic figures/50 high power fields.